Six Candidate miRNAs Associated With Early Relapse in Pediatric B-Cell Acute Lymphoblastic Leukemia - AMANKWAH, ERNEST K. (Anticancer Res, 2020)
BACKGROUND/AIM: Few studies have evaluated the role of miRNAs in pediatric acute lymphoblastic leukemia (ALL) relapse and a consensus of a clinically significant miRNA signature is yet to be identified. In this study, we evaluated miRNAs associated with pediatric B-ALL early relapse in two independent sample sets. MATERIALS AND METHODS: We performed global miRNA profiling on diagnostic bone marrow specimens from six early relapse (≤3 years after diagnosis) and six age- and cytogenetics-matched prolonged remission (≥4 years) patients (first set) and an independent set of 14 early relapse and 14 matched prolonged remission specimens (second set). RESULTS: Twelve and 39 top differentially expressed miRNAs were observed in the first and second sets, respectively; however, there was no overlap between the top candidates. In post-hoc analyses six miRNAs (miR-101–3p, miR-4774–5p, miR-1324, miR-631, miR-4699–5p and miR-922) among the top candidates in the second, but not the first set, were consistently upregulated in early relapse compared to remission specimens in both first (fold change=1.13–2.19, q<0.38) and second (fold change=1.48–4.78, all q<0.05) sets. Four (miR-631, mir-101–3p, miR-922 and miR-1324) of these miRNAs have been previously implicated in key functional oncogenic pathways in adult cancers. CONCLUSION: This study suggests that six candidate miRNAs, not previously implicated in pediatric ALL, are associated with early relapse in pediatric B-ALL. Validation and investigation of mechanistic roles of these miRNAs in a larger cohort are warranted, so that they may be used as prognostic markers for early relapse of pediatric B-ALL.